Incidence of acute kidney injury after teicoplanin– or vancomycin– and piperacillin/tazobactam combination therapy: A comparative study using propensity score matching analysis. Issue 12 (December 2021) - Sazanami, Kohei; Inose, Ryo; Yagi, Tatsuya; Dote, Satoshi; Horiuchi, Nozomu; Kobayashi, Yuka; Muraki, Yuichi
Abstract: Introduction: Combination therapy with vancomycin (VCM) and piperacillin/tazobactam (PIPC/TAZ) increases the risk of acute kidney injury (AKI). Teicoplanin (TEIC) has a lower risk of AKI than VCM. Currently, the difference in AKI risk after TEIC–PIPC/TAZ combination therapy and VCM–PIPC/TAZ combination therapy is controversial. This study aimed to compare AKI incidence after treatment with these two drug combinations using propensity score matching analysis. Methods: This single-center cohort study used data extracted from patients' medical records. We included patients who received TEIC–PIPC/TAZ therapy (TEIC group) or VCM–PIPC/TAZ therapy (VCM group). After propensity score matching, AKI incidence, AKI stage, 30-day mortality, and time to AKI incidence were compared between the groups. Results: After propensity score matching, 94 patients were matched in each group. AKI incidence was significantly lower in the TEIC group than in the VCM group (10.6% vs. 23.4%, odds ratio [95% confidence interval]: 0.39 [0.17–0.88], p =  0.03). AKI stage, 30-day mortality, and time to AKI incidence were not significantly different between the groups. Conclusions: This study suggested that AKI incidence may be lower in patients undergoing combination therapy with TEIC–PIPC/TAZ than in those receiving therapy with VCM–PIPC/TAZ. To prevent the occurrence of AKI, clinicians may need to choose TEIC instead of VCM for patients receiving PIPC/TAZ.